2005
DOI: 10.2166/wst.2005.0334
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of bromate in groundwater with an ex situ suspended growth bioreactor

Abstract: A potential remediation technique for groundwater contaminated by bromate has been investigated, utilising biological bromate reduction to bromide by augmentation of indigenous microbial populations. This technique, involving addition of a carbon source to contaminated groundwater, is being developed as an ex-situ methodology analogous to commercial denitrification systems, but may also have in-situ applications. Trials have focussed on a laboratory-scale anaerobic suspended growth chemostat system, investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Several approaches have been evaluated to eliminate bromate pollution, such as filtration [6], UV irradiation [7], photo-catalytic decomposition [8], coagulation [9], ion exchange [10], biodegradation [11,12], chemical and electrochemical reduction [13,14]. Among them, the use of electrochemical approach is considered attractive, since they are relatively clean, environment-friendly and often cost efficient [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been evaluated to eliminate bromate pollution, such as filtration [6], UV irradiation [7], photo-catalytic decomposition [8], coagulation [9], ion exchange [10], biodegradation [11,12], chemical and electrochemical reduction [13,14]. Among them, the use of electrochemical approach is considered attractive, since they are relatively clean, environment-friendly and often cost efficient [15].…”
Section: Introductionmentioning
confidence: 99%
“…The above reaction scheme shows that the initial bromate which is reduced by the reaction (7) can be reproduced from the reactions (8) and (9). The presented scheme of the reduction can explain why the kinetics is more complicated than that predicted by the voltammetric measurements (Fig.…”
Section: Steady-state Electrolytic Experimentsmentioning
confidence: 64%
“…Many methods for the removal of bromate from potable water have been proposed including ion exchange [5], nanofiltration [6], UV irradiation [7], photocatalytic degradation [8], coagulation with Al 3+ and Fe 3+ [9], chemical reduction with a variety of reducing agents, such as Fe 2+ [10], biological degradation [11], as well as electrochemical reduction on various cathodes [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The observed microbial reduction was most likely catalyzed by microorganisms capable of utilizing the endogenous organic substrate in the inoculum as electron donor. Microbial reduction of bromate with electron-donating substrates such as acetate (van Ginkel et al 2005a), glucose (Butler et al 2005b), and with H 2 gas (Nerenberg and Rittmann 2004;van Ginkel et al 2005b) has been reported in recent studies. The assay lacking S 0 had a longer lag phase as well as a lower bromate removal rate than the treatment with added S 0 , indicating that the S 0 -dependent reduction of bromate was more effective compared to the microbial reduction utilizing the low levels of complex endogenous organic matter in the inoculum.…”
Section: Abiotic Reduction Of Bromate By Sulfidementioning
confidence: 93%
“…Reduction of bromate to the benign ion bromide (Br -) can be performed by mixed-and pure cultures of denitrifying bacteria when supplemented with ethanol as the energy and carbon source (Hijnen et al 1995(Hijnen et al , 1999. Other organic electron donors such as glucose and acetate have also been used for the biological reduction of bromate by indigenous groundwater microbial populations and anaerobic mixed microbial cultures, respectively (Butler et al 2005b;van Ginkel et al 2005a). However, the use of organic electrondonating substrates can potentially leave behind organic residuals that can contribute to the formation of toxic disinfection byproducts during chlorination (Ju et al 2007).…”
Section: Introductionmentioning
confidence: 99%